2013
DOI: 10.17742/image.mother.4-2.2
|View full text |Cite
|
Sign up to set email alerts
|

From Soap Opera to Reality Programming: Examining Motherhood, Motherwork and the Maternal Role on Popular Television

Abstract: Representations of motherhood dominate the television landscape in a variety of popular genre texts, and as such it is important that we consider the ways in which these women are being constructed and circulated on the small screen. Indeed, although much work has been done to investigate the depiction of women on television, little research exists to account for the portrayal of mothering, motherhood, and the maternal role. With this in mind, this article introduces extant literature concerning the representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
7
0
2
Order By: Relevance
“…These negative feelings and high pressure might impact mothers' parental self-efficacy (e.g., Germic et al, 2021;Marulli, 2021). This Mask of Motherhood, as Susan Maushart called it, is not only observable among existing mothers, but also among expecting mothers (Feasey, 2013). We therefore want to test the association between visiting mommy influencer profiles (Cfr.…”
Section: Social Learning Theory and Parental Self-efficacymentioning
confidence: 99%
“…These negative feelings and high pressure might impact mothers' parental self-efficacy (e.g., Germic et al, 2021;Marulli, 2021). This Mask of Motherhood, as Susan Maushart called it, is not only observable among existing mothers, but also among expecting mothers (Feasey, 2013). We therefore want to test the association between visiting mommy influencer profiles (Cfr.…”
Section: Social Learning Theory and Parental Self-efficacymentioning
confidence: 99%
“…I have previously suggested that soap operas present 'good enough' mothers rather than a more romanticised ideal of maternal care, because in many cases these women are seen to look after their children, but not at the expense of their social, sexual or financial desires (Feasey 2013). My point was that these mothers tend to the physical and emotional needs of their children, often under trying financial and familial circumstances, but they do not do so to the detriment of their independence or individual identity.…”
Section: People In Soap Operas Who Have Children At the Drop Of A Hatmentioning
confidence: 99%
“…It is not my intention to look in detail at the pros and cons of each available media method -indeed, there are a myriad of successful volumes dedicated to that particular topic (Priest 2010;Berger 2013)rather, this chapter will give a brief overview of existing ethnographic studies that present women's responses to gendered media genres, namely, harlequin romances, celebrity gossip magazines, female film stardom and soap opera, before outlining the ways in which I looked to find suitable participants, listen to their voices and present their views as they relate to maternal depictions on the small screen. 8 Chapter 1 I have previously examined representations of motherhood on popular television and considered the ways in which such depictions inform the 'good' mother myth in an age of intensive mothering and the professionalism of motherwork, paying particular attention to the ways in which maternal images might be seen and understood by the mother in the audience (Feasey 2011(Feasey , 2012a(Feasey , 2013. Although this work was crucial in presenting the relationship between media and motherhood studies and in foregrounding historic and more contemporary representations of motherhood in the entertainment area in relation to the changing social, sexual and political context, what was missing here of course was the voice of the audience.…”
Section: Introductionmentioning
confidence: 99%
“…Gender is one of the strongest and most hard-wired stereotypes resources (Kurzban et al, 2001;Schneider, 2005), and so gender stereotype is extensively used by media across the world (Kitsa & Mudra, 2020;Neto & Pinto, 1998;Ter Bogt et al, 2010). In the mainstream media, women are represented as sexual objects or in the frame of motherhood, whereas men are portrayed as sex-driven, aggressive, and dominant (Feasey, 2013;Giaccardi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%